The Relationship between Anti-Factor Xa Level and Clinical Outcome in Patients Receiving Enoxaparine Low Molecular Weight Heparin to Prevent Deep Vein Thrombosis after Hip Replacement - Levine, M N; Planes, A; Hirsh, J; Goodyear, M; Vochelle, N; Gent, M (Thrombosis and Haemostasis, 1989)
Studies in experimental animals have demonstrated that there is a relationship between levels of low molecular weight (LMW) heparin and both bleeding and inhibition of thrombosis. The relationship between these outcomes and ex vivo anti-factor Xa levels has been examined in 163 patients undergoing total hip replacement who were given prophylaxis once daily with a LMW heparin (enoxaparine). Fifty patients received 60 mg of enoxaparine and 113 received 40 mg, both regimens being administered subcutaneously once daily. Blood samples for anti-factor Xa levels were collected 12 hours after the injection on the day of surgery and on days 1, 3 and 6, postoperatively. The incidence of wound hematoma was 5.3% when the maximum anti-factor Xa level was ≤0.2 units per ml, but increased to 24.5% when the anti-factor Xa level exceeded 0.2 units per ml, P = 0.0008. The incidence of postoperative thrombosis was low (6.3%) if the minimum anti-factor Xa level exceeded 0.1 units per ml, but increased to 14.6% when ≤0.1 units per ml, and to 18.8% if the anti-factor Xa level was ≤0.05 units per ml. Regression analysis revealed that there was a statistically significant relationship between anti-factor Xa level and wound hematoma, P = 0.002 and anti-factor Xa level and thrombosis, P = 0.03. These findings suggest that when enoxaparine is administered as a once daily subcutaneous injection, the 12 hour anti-factor Xa level should not exceed 0.2 units per ml to minimize bleeding and levels >0.05 units per ml should be obtained to optimize efficacy.
Keywords: Low molecular weight heparin; Hip replacement; Deep vein thrombosis